Analysing high-throughput sequencing data in Python with HTSeq 2.0 - Putri, Givanna H; Anders, Simon; Pyl, Paul Theodor; Pimanda, John E; Zanini, Fabio (Bioinformatics (Oxford, England), 2022)
HTSeq 2.0 provides a more extensive application programming interface including a new representation for sparse genomic data, enhancements for htseq-count to suit single-cell omics, a new script for data using cell and molecular barcodes, improved documentation, testing and deployment, bug fixes and Python 3 support. HTSeq 2.0 is released as an open-source software under the GNU General Public License and is available from the Python Package Index at https://pypi.python.org/pypi/HTSeq. The source code is available on Github at https://github.com/htseq/htseq. Supplementary data are available at Bioinformatics online.